Alyssum homolocarpum seed gum-polyvinyl alcohol biodegradable composite film: Physicochemical, mechanical, thermal and barrier properties. (2nd January 2017) - Monjazeb Marvdashti, Leila; Koocheki, Arash; Yavarmanesh, Masoud
Graphical abstract: Highlights: ⿢ Blending Alyssum homolocarpum seeds gum (AHSG) with PVA seems to be a promising strategy to obtain a biodegradable package. ⿢ AHSG improved the moisture resistance but reduced the oxygen permeability of film. ⿢ Formation of hydrogen bonds between polymers gave a homogeneous structure to the film. ⿢ Water sorption of film reduced with addition of AHSG. Abstract: Films made from Alyssum homolocarpum seeds gum (AHSG) have poor mechanical and barrier (to oxygen) properties. In the present study poly vinyl alcohol (PVA) was used to improve the physicochemical properties of AHSG films. Results indicated that the addition of PVA significantly increased the moisture content, solubility, elongation at break (EB) and transparency while it decreased the density, oxygen permeability, chroma, water contact angle and Young modulus of AHSG based films. Films with higher AHSG to PVA ratios had lower water vapor permeability (WVP). The light barrier measurements presented low values of transparency at 600 nm for PVA/AHSG films, indicating that films were very transparent while they had excellent barrier properties against UV light. Results for FTIR, DSC and SEM showed a clear interaction between PVA and AHSG, forming a new material. These results indicated that PVA/AHSG blend films had good compatibility.